2009
DOI: 10.1124/dmd.109.027409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the TATA Box and Upstream Phenobarbital-Responsive Enhancer Module of the UGT1A1 Promoter Have Combined Effects on UDP-Glucuronosyltransferase 1A1 Transcription Mediated by Constitutive Androstane Receptor, Pregnane X Receptor, or Glucocorticoid Receptor in Human Liver

Abstract: ABSTRACT:Transcription of UDP-glucuronosyltransferase (UGT) 1A1 is regulated by the transcription factors, constitutive androstane receptor (CAR), pregnane X receptor (PXR), glucocorticoid receptor (GR), hepatocyte nuclear factor (HNF) 1␣, and HNF4␣. The purpose of this study was to determine whether the genetic polymorphisms in the RNA polymerase II core promoter and the upstream phenobarbital-responsive element module (PBREM) of the UGT1A1 promoter have combined effects on UGT1A1 transcription mediated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The allele frequency of c.-3279T>G is as high as 0.39 in the general Caucasian population [12], which is similar to that in the Taiwanese population (0.37) [5]. However, such a mutation is often ignored when the UGT1A1 gene is analyzed [5].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The allele frequency of c.-3279T>G is as high as 0.39 in the general Caucasian population [12], which is similar to that in the Taiwanese population (0.37) [5]. However, such a mutation is often ignored when the UGT1A1 gene is analyzed [5].…”
Section: Discussionmentioning
confidence: 90%
“…Sugatani et al [8 ]and Li et al [12 ]reported that the c.-3279T>G polymorphism is associated with a decrease in UGT transcription and that individuals carrying that polymorphic mutation are at a high risk of developing Gilbert's syndrome and irinotecan toxicity. The allele frequency of c.-3279T>G is as high as 0.39 in the general Caucasian population [12], which is similar to that in the Taiwanese population (0.37) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Residual UGT1A1 activity in this patient may therefore be derived from the other allele that appears to have a normal coding region but may contain the UGT1A1Ã28 promoter polymorphism. This allele might also contain additional polymorphisms such as the g.À3279T4G of which was reported recently that, in combination with the UGT1A1Ã28 polymorphism, results in further reduction of UGT1A1 expression [Li et al, 2009].…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, in the gtPBREM cluster a polymorphism (T3279G) was found in linkage disequilibrium with the UGT1A1*28 polymorphism which synergistically lowers UGT1A1 expression [84,85].…”
Section: Possible Autoregulatory Control Of Ugt1a1 By Bilirubinmentioning
confidence: 99%